Herramientas digitales en el periodismo deportivo local y su incidencia en la opinión pública de Riobamba, septiembre 2017-febrero 2018 - Navarrete Paredes, David Patricio (2018)
Sport undoubtedly has a superior social connotation on other information matters, at the time of the existing predominance, the development of social media has not left aside the sports spaces that are involved with their spaces in digital media. This research is a collection of historical data about the media starting from the printed media that were born from the invention of the Gutenberg printing press, reaching the radio that took the information to new extracts of society due to at the beginning the written press was available only to the literate people of the time. This work includes the invention of television from black and white to color with a great relevance first event such as a Soccer World Cup that was broadcast from America in 1970 where Brazil was the champion. Two instances are the main axes on which the present investigation was worked and are the tools used in local sports journalism and how it is received in the different spaces of public opinion in the city. The data collected announce that digital media have a tendency to grow compared to traditional media related to the issue of information consumption, in addition to an important fact is that citizens have the perception that digital media influence in the same way or at the same level as traditional media.